Plasma extracellular vesicles detected by Single Molecule array technology as a liquid biopsy for colorectal cancer. Issue 1 (1st January 2020) - Wei, Ping; Wu, Fei; Kang, Bin; Sun, Xiaohua; Heskia, Fabienne; Pachot, Alexandre; Liang, Ji; Li, Dawei
ABSTRACT: Circulating extracellular vesicles (EVs) were recognized as a promising source of diagnostic biomarker. However, there are limited studies published in this area, partly due to the limited number of detection platforms capable of detecting extracellular vesicles. In this study, extracellular vesicle immunoassays were developed using the Single Molecule array technology (SiMoa) and their clinical applications to cancer diagnosis were evaluated. Two extracellular vesicle detection assays, CD9-CD63 and Epcam-CD63, were designed to detect universal extracellular vesicles and tumour-derived extracellular vesicles, respectively. Our results show that CD9-CD63 and Epcam-CD63 SiMoa assays specifically detect extracellular vesicles but not free proteins with high sensitivities. The Epcam-CD63 levels detected in cancer cell culture media were consistent with levels of Epcam-expressing EVs isolated from the same cancer cell lines and detected by Western blot. Furthermore, the assays distinguish cancerous from non-cancerous plasma samples. The highest CD9-CD63 and Epcam-CD63 signals were observed in colorectal cancer patients comparing to healthy and benign controls. Both assays showed superior diagnostic performance for colorectal cancer. In addition, our results show that CD9-CD63 detection is an independent prognosis factor for both progression free survival and overall survival, while Epcam-CD63 detectionis an independent prognosis factor for OS.